Empowerment Design of Putri Gemilang Village-Owned Enterprises Community Based on Asset-Based Community Development - Mhd Safuan; Nurus Shalihin; Walan Yudhiani (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2023)
Asset-based community empowerment has become a necessity as communities often possess and utilize their potential effectively. This study aims to illustrate the asset-based community empowerment process conducted within the Badan Usaha Milik Desa Puteri Gemilang community. The study focuses on the stage of building community awareness. By utilizing the Assed-Based Community Development (ABCD) mentoring model, this study identifies strategies for raising awareness within the Badan Usaha Milik Desa Puteri Gemilang community. With this ABCD approach, the community achieves something new, such as the formation of teamwork cohesion, the establishment of strong commitment, the cultivation of critical thinking, and the development of future program designs.